Transmission routes and patterns of helicobacter pylori. Issue 1 (16th January 2023) - Duan, Miao; Li, Yueyue; Liu, Jing; Zhang, Wenlin; Dong, Yi; Han, Zhongxue; Wan, Meng; Lin, Minjuan; Lin, Boshen; Kong, Qingzhou; Ding, Yuming; Yang, Xiaoyun; et al.
Abstract: Background and objective: Helicobacter pylori ( H. pylori ), a gram‐negative bacterium that colonizes the stomach, can cause chronic gastritis and peptic ulcers, as well as gastric cancer as a Class I carcinogen. However, the modes of H. pylori transmission are not clear. This review aims to clarify the transmission routes and patterns of H. pylori and identify efficacious prevention measures. Methods: Studies of H. pylori transmission were identified using PubMed, the Web of Science, and Cochrane Central; the retrieval deadline was October 2022. Results: The transmission routes of H. pylori are discussed, focusing on the five primary transmission routes, namely fecal–oral, oral–oral, gastric–oral, anal–oral, and genital–oral. We propose that H. pylori is contracted through multiple transmission routes. Additionally, we summarize the key transmission patterns of H. pylori, including person‐to‐person and animal‐to‐human transmission, as well as foodborne and occupational exposure. Conclusion: Fecal–oral appears to be the most common H. pylori transmission routes. Although the oral–oral pathway is also important, the evidence does not support that this route of transmission is universal. The gastric–oral route occurs primarily in children and patients who are prone to vomiting. Meanwhile, the anal–oral and genital–oral routes remain hypothetical. Person‐to‐person and foodborne infections represent the predominant transmission patterns of H. pylori, whereas strong environmental and occupational limitations are associated with animal‐to‐human and occupational exposure.